The Paraventricular Thalamus: A Potential Sensor and Integrator of Emotionally Salient Early-Life Experiences - Cassandra L. Kooiker (Frontiers in Behavioral Neuroscience, 2021)
Early-life experiences influence a broad spectrum of behaviors throughout the lifespan that contribute to resilience or vulnerability to mental health disorders. Yet, how emotionally salient experiences early in life are encoded, stored, and processed and the mechanisms by which they influence future behaviors remain poorly understood. The paraventricular nucleus of the thalamus (PVT) is a key structure in modulating positive and negative experiences and behaviors in adults. However, little is known of the PVT’s role in encoding and integrating emotionally salient experiences that occur during neonatal, infancy, and childhood periods. In this review, we (1) describe the functions and connections of the PVT and its regulation of behavior, (2) introduce novel technical approaches to elucidating the role of the PVT in mediating enduring changes in adult behaviors resulting from early-life experiences, and (3) conclude that PVT neurons of neonatal rodents are engaged by both positive and negative emotionally salient experiences, and their activation may enduringly govern future behavior-modulating PVT activity during emotionally salient contexts.